Syndicate training method for safety competencies of workers in Oyo State (2018)
Safety trainings have been observed not to bring desired reduction of accidents rates nor improved safety competencies of workers in the construction industry. It is of major concern if this could be as a result of the wrong methodology used in executing these safety trainings. The paper determined the effects of syndicate training method (STM) on occupational health and safety competencies of workers in the construction industry in Oyo State, Nigeria. It adopted the pretest-postest, control group quasi experimental design. Purposive sampling technique was employed in selecting three reputable construction organisations in Oyo State. The workers in the two organizations who met the study 's inclusion criteria were randomised into STM, (12) and Lecture method (12) (Control) groups while treatment lasted eight weeks. Construction Industry Occupational Health and Safety Competencies Questionnaire (r= 0.85) and Occupational Health and Safety Competencies Scale (r=0.78) were used in collecting data for the study. Data analysis was done using ANCO VA at 0.05 level of significance. There was a significant main effect of treatment on occupational health and safety competencies of construction workers (F(i, 19)= .225, P<0.05, rf= .029). The syndicate training method improved the occupational health and safety competencies of the construction workers. Therefore, the training method should be employed regularly in safety trainings to achieve improved occupational health and safety competencies -workers